1987
DOI: 10.1063/1.453184
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic solvent effects on outer-sphere electron transfer

Abstract: In this paper we present the results of a theoretical study of outer-sphere electron transfer (ET) in a polar solvent, with the modification of the nuclear states by the change in the charge distribution originating solely from the response of the exterior medium. The model Hamiltonian for the system corresponds to two parabolic diabatic potential surfaces with adiabatic coupling between them. The real-time path integral formalism is utilized to derive the general expressions for the influence functional of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
325
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 529 publications
(344 citation statements)
references
References 41 publications
18
325
1
Order By: Relevance
“…This relationship has been stated before in [13,33] without detailed derivation. For the sake of completeness we provide the derivation here employing a different, simple approach.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 2 more Smart Citations
“…This relationship has been stated before in [13,33] without detailed derivation. For the sake of completeness we provide the derivation here employing a different, simple approach.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…But as Bader et al pointed out [33], the dispersed polaron method is a semiclassical approximation, which assume [Ê R ,Ê P ] = 0, whereÊ R andÊ P are explained in (13) and (14), so that it only gives good results in the classical limit i.e., at high temperatures, but overestimates the tunneling correction at low temperatures. As a matter of fact, one can show that Warshel et al's treatment is an approximation of the spin-boson model at high temperature.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a decisive development of the preceding work (19,20,25,26), we offer unique kinetic data obtained through temperature-and pressure-variation and the mechanistic analysis through a unique global fitting procedure accounting for ET at different SAM thickness, temperature, and pressure conditions that provided the variation of the reduced ET rate constant over almost five orders of magnitude. Importantly, our previous work demonstrated that Au-deposited SAMs can withstand pressure-related stress within 5 to 150 MPa (27, 28, 34).The rate constant, k et , for nonbiological and biological ET may be cast in a thermally activated Arrhenius form that is valid within the range of commonly used temperatures (1,3,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45):where ΔG Ã a is an activation free energy for reaching the transition state, which arises from the complete Franck-Condon weighted density of states and is connected with the medium's dielectric (cumulative sum) response, and A is a preexponential factor whose form is specific for the ET mechanism (see below) (1,3,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45). Previous studies that exploited SAM-coated electrodes revealed two kinds of phenomenological behavior (17)(18)(19)(20)(21)(22)(24)(25)(26)…”
mentioning
confidence: 99%
“…The conjecture that this reaction takes place in the strongly adiabatic limit [26][27][28] has partly motivated us to undertake this research. For jet-cooled derivative compounds of fluoroprobe, the excitation spectra have recently been published [29].…”
Section: Introductionmentioning
confidence: 99%